Different Profiles of Spatial Navigation Deficits In Alzheimer’s Disease Biomarker-Positive Versus Biomarker-Negative Older Adults With Amnestic Mild Cognitive Impairment - Laczó, Martina; Martinkovic, Lukas; Lerch, Ondrej; Wiener, Jan M.; Kalinova, Jana; Matuskova, Veronika; Nedelska, Zuzana; Vyhnalek, Martin; Hort, Jakub; Laczó, Jan (Frontiers in Aging Neuroscience, 2022)
Background Spatial navigation impairment is a promising cognitive marker of Alzheimer’s disease (AD) that can reflect the underlying pathology. Objectives We assessed spatial navigation performance in AD biomarker positive older adults with amnestic mild cognitive impairment (AD aMCI) vs. those AD biomarker negative (non-AD aMCI), and examined associations between navigation performance, MRI measures of brain atrophy, and cerebrospinal fluid (CSF) biomarkers. Methods A total of 122 participants with AD aMCI (n = 33), non-AD aMCI (n = 31), mild AD dementia (n = 28), and 30 cognitively normal older adults (CN) underwent cognitive assessment, brain MRI (n = 100 had high-quality images for volumetric analysis) and three virtual navigation tasks focused on route learning (body-centered navigation), wayfinding (world-centered navigation) and perspective taking/wayfinding. Cognitively impaired participants underwent CSF biomarker assessment [amyloid-β1–42, total tau, and phosphorylated tau181 (p-tau181)] and amyloid PET imaging (n = 47 and n = 45, respectively), with a subset having both (n = 19). Results In route learning, AD aMCI performed worse than non-AD aMCI (p < 0.001), who performed similarly to CN. In wayfinding, aMCI participants performed worse than CN (both p ≤ 0.009) and AD aMCI performed worse than non-AD aMCI in the second task session (p = 0.032). In perspective taking/wayfinding, aMCI participants performed worse than CN (both p ≤ 0.001). AD aMCI and non-AD aMCI did not differ in conventional cognitive tests. Route learning was associated with parietal thickness and amyloid-β1–42, wayfinding was associated with posterior medial temporal lobe (MTL) volume and p-tau181 and perspective taking/wayfinding was correlated with MRI measures of several brain regions and all CSF biomarkers. Conclusion AD biomarker positive and negative older adults with aMCI had different profiles of spatial navigation deficits that were associated with posterior MTL and parietal atrophy and reflected AD pathology.